Strategi Islamic Marketing Mix Wisata Kampung Mandor Plaosan Cluwak Pati - Sutriani, Endang (JIOSE: Journal of Indonesian Sharia Economics, 2024)
This research aims to explain the Islamic marketing mix strategy of Kampung Foreman Tourism Plaosan Cluwak Pati Village. This study uses a descriptive qualitative research method with data collection techniques through interviews, observations and documentation. The results of this study show that the marketing strategy used by the management of Kampung Mandor Tourism is known as the term Islamic marketing mix which consists of 9P, namely; Product, Price, Promotion, Place, People, Process, Physical evidence, Promise and Patience. The marketing strategies carried out by the management include being carried out online, utilizing social media Instagram and WhatsApp. The obstacles faced by the manager in marketing the foreman village tourism are in terms of the products offered such as food menus and parking spaces that have not been maximized. Therefore, the management is trying to develop tourism so that there is a new atmosphere and visitors feel interested, satisfied, safe and comfortable.